1968
DOI: 10.1161/01.res.22.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin in Chronic Experimental Heart Failure and during Renal Sodium "Escape" from Mineralocorticoids

Abstract: A striking increase in the plasma renin level occurred in dogs with low output right heart failure secondary to tricuspid insufficiency and pulmonic stenosis and in three of five animals with high output failure produced by a large arteriovenous fistula. When dogs with a small arteriovenous fistula were given daily injections of DOCA, the renal sodium "escape" phenomenon occurred. In these animals, the level of plasma renin was suppressed during DOCA administration both during the initial period of sodium rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Enhanced sodium reabsorption by the proximal tubule has been thought to be the mechanism causing sustained salt retention in dogs with an aortato-vena cava fistula [11]. Our data demonstrate that reabsorption by the proximal tubule was indeed enhanced in the A-V fistula rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Enhanced sodium reabsorption by the proximal tubule has been thought to be the mechanism causing sustained salt retention in dogs with an aortato-vena cava fistula [11]. Our data demonstrate that reabsorption by the proximal tubule was indeed enhanced in the A-V fistula rats.…”
Section: Discussionsupporting
confidence: 51%
“…From clearance determinations in patients with edema of different origin, Bell et al [6] and Schedl and Barrter [22] have concluded that the major site of salt and water retention is the proximal tubule. Similarly, an enhanced rate of sodium reabsorption by the proximal tubule has been suggested to be the mechanism causing salt retention in dogs with either high-output heart failure [11] or thoracic caval constriction [7], However, recent micropuncture studies in dogs with edema and ascites due to an aorta-to-vena cava fistula [23] or to chronic caval constriction [3,17] have clearly demonstrated that proximal tubular function is normal in these models of salt retention with regard to both fractional and absolute sodium reabsorption. Furthermore, the limited natriuretic response of these animals to acute extracellular fluid volume expansion is not caused by failure to decrease sodium reabsorption in the proximal tubule [3,17,23].…”
mentioning
confidence: 99%
“…Activation of the RAA system has been demonstrated in chronic and subacute forms of experimental heart failure [2,15,19,27]. It has been shown clinically in complicated acute myocardial infarction [22] and in chronic congestive heart failure [5,9,12,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Genest et al [37] used a balloon to transiently obstruct venous return to the right atria of dogs and found a three fold increase in plasma renin activity. Johnston et al [52] found increased plasma renin levels in dogs with low cardiac output secondary to tricuspid insufficiency and pulmonic stenosis. In dogs with arteriovenous fistulas and high output cardiac failure, three of five animals showed increased plasma renin activity [52], In DOCA-treated dogs which developed a venous con gestive state after the creation of arteriovenous fistula, but did not have elevated right atrial pressures plasma renin activity remained low [52], Davis et al [100] using larger arteriovenous fistulas in dogs demonstrated consistent rise in renin secretion from 600 to 2,000 ng A/min.…”
Section: Edematous Statesmentioning
confidence: 98%
“…Johnston et al [52] found increased plasma renin levels in dogs with low cardiac output secondary to tricuspid insufficiency and pulmonic stenosis. In dogs with arteriovenous fistulas and high output cardiac failure, three of five animals showed increased plasma renin activity [52], In DOCA-treated dogs which developed a venous con gestive state after the creation of arteriovenous fistula, but did not have elevated right atrial pressures plasma renin activity remained low [52], Davis et al [100] using larger arteriovenous fistulas in dogs demonstrated consistent rise in renin secretion from 600 to 2,000 ng A/min. D avis et al [13] have also demonstrated that the mechanism of increased renin release with caval con striction in dogs with nonfiltering kidneys is mediated by a baroreceptor mechanism.…”
Section: Edematous Statesmentioning
confidence: 98%